Water electrolysis for hydrogen production: from hybrid systems to self-powered/catalyzed devices - Ren, Jin-Tao; Chen, Lei; Wang, Hao-Yu; Tian, Wen-Wen; Yuan, Zhong-Yong (Energy & environmental science, 2024)
The electrocatalytic splitting of water holds great promise as a sustainable and environmentally friendly technology for hydrogen production. However, the sluggish kinetics of the oxygen evolution reaction (OER) at the anode significantly hampers the efficiency of this process. In this comprehensive perspective, we outline recent advancements in innovative strategies aimed at improving the energy and economic efficiency of conventional water electrolysis, thereby facilitating efficient hydrogen generation. These novel strategies mainly include: (i) sacrificial-agent-assisted water electrolysis, which integrates thermodynamically favorable small molecules to replace the OER while simultaneously degrading pollutants; (ii) organic upgrading-assisted water electrolysis, wherein thermodynamically and kinetically favorable organic oxidation reactions replace the OER, leading to the production of high-value chemicals alongside hydrogen; (iii) self-powered electrolysis systems, achieved by coupling water splitting with metal-based batteries or fuel cells, enabling hydrogen production without the need for additional electricity input; and (iv) self-catalyzed electrolysis systems driven by the spontaneous metal oxidation at the anode, which provides electrons for hydrogen evolution at the cathode. In particular, we emphasize the design of electrocatalysts using non-noble metal elements, elucidate the underlying reaction mechanisms, and explore the construction of efficient electrolyzers. Additionally, we discuss the prevailing challenges and future prospects, aiming to foster the development of electrocatalytic systems for highly efficient hydrogen production from water in the future. This perspective highlights recent advancements in innovative strategies to provide valuable insights into the potential for energy-saving hydrogen production through water electrolysis.